Encapsulation of bacterial cells in cytoprotective ZIF-90 crystals as living composites. (March 2021) - Li, H.; Kang, A.; An, B.; Chou, L.-Y.; Shieh, F.-K.; Tsung, C.-K.; Zhong, C.
Abstract: Exploiting metal-organic frameworks (MOFs) as selectively permeable shelters for encapsulating engineered cells to form hybrid living materials has attracted increasing attention in recent years. Optimizing the synthesis process to improve encapsulation efficiency (EE) is critical for further technological development and applications. Here, using ZIF-90 and genetically engineered Escherichia coli (E. coli) as a demo, we fabricated E. coli @ZIF-90 living composites in which E. coli cells were encapsulated in ZIF-90 crystals. We illustrated that ZIF-90 could serve as a protective porous cage for cells to shield against toxic bactericides including benzaldehyde, cinnamaldehyde, and kanamycin. Notably, the E. coli cells remained alive and could self-reproduce after removing the ZIF-90 crystal cages in ethylenediaminetetraacetic acid, suggesting a feasible route for protecting and prolonging the lifespan of bacterial cells. Moreover, an aqueous multiple-step deposition approach was developed to improve EE of the E. coli @ZIF-90 composites: the EE increased to 61.9 ± 5.2%, in contrast with the efficiency of the traditional method (21.3 ± 4.4%) prepared with PBS buffer. In short, we develop a simple yet viable strategy to manufacture MOF-based living hybrid materials that promise new applications across diverse fields. Graphical abstract: Encapsulation of bacterial cells in cytoprotective ZIF-90 crystals as living composites. Image 1